Diversity of endophytic fungi in Syzygium aqueum - Ummi Hiras Habisukan; ELFITA ELFITA; HARY WIDJAJANTI; ARUM SETIAWAN; ALFIA R. KURNIAWATI (Society for Indonesian Biodiversity, 2021)
Abstract. Habisukan UH, Elfita, Widjajanti H, Setiawan A, Kurniawati AR. 2021. Diversity of endophytic fungi in Syzygium aqueum. Biodiversitas 22: 1129-1137. Exploring endophytic fungi may provide alternative, plant-based ethnomedicines. The discovery of endophytic fungi can produce many plant-derived drugs that give new horizons to the pharmaceutical industry for the availability and production of such medicines on a large scale. Extracts from Syzygium aqueum Alston (jambu air), a fruit-bearing plant native to Indonesia, have long been used in traditional medicine. Therefore, the purpose of this study was to identify, and investigate, the antimicrobial activity of the endophytic fungi found in S. aqueum. Results revealed that total16 fungi were isolated . Fungal endophytes were identified through morphological characterization and subsequently compared with key fungal identification books. The ethyl acetate extracts of the isolated endophytic fungi were screened for their antimicrobial activity through paper disc diffusion assay fungi isolated from S. aqueum were identified as: Aspergillus niger (Isolate code R21, R41, T72), Cylindrocarpon sp. (Isolate code R11, R31), Trichoderma aureoviridae (Isolate code T11), Trichoderma harzianum (Isolate code T21), Trichoderma sp. (Isolate code T31), Pestalotia sp. (Isolate code T41and T62), Beltrania sp. (Isolate code T52), Chaetomium sp. (Isolate code L11), Cochliobolus sp. (Isolate code L22), Penicillium sp. (Isolate code L32), Cylindrocladium sp. (Isolate code L42), and an unidentified Ascomycota (T51). The values of Shannon-Weiner and Simpson diversity indexes for the overall fungal community were H?=2.133 and 1-D=0.859 respectively. All isolates showed potential antimicrobial activity against Escherichia coli, Salmonella Typhi, and Staphylococcus aureus, but the lowest activity against Candida albicans. The results indicate that the bioactive compounds and secondary metabolites of these isolates should be further investigated for pharmaceutical applications.